PEMEROLEHAN BAHASA ANAK AKIBAT PENGARUH FILM KARTUN ( SUATU TINJAUAN PSIKOLINGUISTIK) - Nurjanah, Siti; Millatuddiiniyyah, Millatuddiiniyyah; Nofianty, Nofianty (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Children's language acquisition was influenced by the environment. The movies they watch can also affect their language. This was seen from the use of words, phrases, and sentences of the films they imitate and generalize in dailly conversations. Data were collected from four to six years old in Diniah Takmiliyah Al-Hidayah, Pangkalan village, Ngamprah sub-district, West Bandung regency. This research method was descriptive qualitative. At the data gathering stage, the researchers used the (simak method) of listening to the children's speech from watching children's cartoon movies. Therefore, this research related to the acquisition of the language of children due to their limitations in processing information in the form of language.